Smart Adsorbents for Aquatic Environmental Remediation. Issue 34 (25th April 2021) - Nazarzadeh Zare, Ehsan; Mudhoo, Ackmez; Ali Khan, Moonis; Otero, Marta; Bundhoo, Zumar Muhammad Ali; Patel, Manvendra; Srivastava, Anju; Navarathna, Chanaka; Mlsna, Todd; Mohan, Dinesh; Pittman, Charles U.; Makvandi, Pooyan; et al.
Abstract: A noticeable interest and steady rise in research studies reporting the design and assessment of smart adsorbents for sequestering aqueous metal ions and xenobiotics has occurred in the last decade. This motivates compiling and reviewing the characteristics, potentials, and performances of this new adsorbent generation's metal ion and xenobiotics sequestration. Herein, stimuli‐responsive adsorbents that respond to its media (as internal triggers; e.g., pH and temperature) or external triggers (e.g., magnetic field and light) are highlighted. Readers are then introduced to selective adsorbents that selectively capture materials of interest. This is followed by a discussion of self‐healing and self‐cleaning adsorbents. Finally, the review ends with research gaps in material designs. Abstract : Smart adsorbents respond to internal (e.g. pH, temperature) and/or external (e.g. magnetic field, light) triggers, and deliver selective adsorption behavior. In this review, the characteristics and adsorption performances of smart adsorbents in taking up aqueous environmental micropollutants are discussed. The self‐healing and self‐cleaning properties of specific smart adsorbents are also discussed in context of their reusability.